Anchoring Mechanism for Capsule Endoscope: Mechanical Design, Fabrication and Experimental Evaluation. - Rehan M; Yeo AG; Yousuf MU; Avci E (MDPI (Basel, Switzerland), 2022)
Capsule endoscopes are widely used to diagnose gut-related problems, but they are passive in nature and cannot actively move inside the gut. This paper details the design process and development of an anchoring mechanism and actuation system to hold a capsule in place within the small intestine. The design centres around the mechanical structure of the anchor that makes use of compliant Sarrus linkage legs, which extend to make contact with the intestine, holding the capsule in place. Three variants with 2 legs, 3 legs and 4 legs of the anchoring mechanism were tested using a shape memory alloy spring actuator (5 mm × ϕ 3.4 mm). The experiments determine that all the variants can anchor at the target site and resist peristaltic forces of 346 mN. The proposed design is well suited for an intestine with a diameter of 19 mm. The proposed design allows the capsule endoscopes to anchor at the target site for a better and more thorough examination of the targeted region. The proposed anchoring mechanism has the potential to become a vital apparatus for clinicians to use with capsule endoscopes in the future.
Keywords: anchoring mechanism; capsule endoscope; locomotion mechanism; robotic capsule